Biochemical changes in athletes during marathon and ultra-marathon races, with special reference to the incidence and prevention of hypoglycaemia - McArthur, Penelope S (MRC/UCT RU for Exercise and Sport Medicine, 2017)
Fats and carbohydrates are the major fuels utilized during exercise and it has been suggested that carbohydrate depletion is the cause of exhaustion during prolonged exercise lasting more than two hours. However, there is some disagreement in the literature as to whether this exhaustion is due either to muscle glycogen depletion or to hypoglycaemia secondary to liver glycogen depletion. I therefore undertook three studies to determine the roles of hypoglycaemia in explaining fatigue in marathon and ultra-marathon runners.